Seasonal abundance of crustaceans associated with artisanal fishery of blue crab (Callinectes sapidus) in Sisal, Yucatan, Mexico - Celis-Sánchez, José Alfredo (2014)
Seasonal abundance and selectivity of the main crustacean species associated with blue crab fishing was studied at the port of Sisal, Yucatan, Mexico. For this purpose, 52 crab traps were used, which were divided into four parallel transects placed 100, 150, 200 and 250 m of the shoreline. Each transect consisted of 13 traps 20 m from each other. Traps were set at dusk and checked at dawn, standardizing the fishing effort to 17 hours/trap/day. A total of 832 organisms from eight species were caught; however, the study was conducted with four commercially important species: Blue Crab (Callinectes sapidus), white crab (C. similis), spider crab (Libinia dubia) and stone crab (Menippe mercenaria), accounting for 60.7%, 13.3%, 11.4%, and 11.6% of the catch, respectively. When dividing the total catch between climatic seasons (dry, rainy, and north wind), significant differences were detected in catch per unit effort (kg trap). The highest catch of C. sapidus and L. dubia was recorded in the dry season, while C. similis and M. mercenaria highest catch was in the north wind season. Most species showed a sex ratio different from 1:1, except for C. similis. Regarding selectivity or size at first catch (L50) values were 148, 90, 60, and 94 mm carapace width for C. sapidus, C. similis, L. dubia and M. mercenaria, respectively.